The impact of volatile oils of three medicinal plants on the bacteria isolated from patients with tonsillitis (Baghdad Science Journal, 2006)
Were collected three types of medicinal plants from their natural habitat after Astkhalasalziot volatile manner steam distillation and determine the quality and quantity of vehicles chemical for each of the oils obtained using a technique JC discouraged when you merge oily thyme and lemon grass against bacteria either when using oils in three did not have a different effect